A histopathologic diagnosis of brain lymphangiomyoma, clinically misdiagnosed as simple angiomyxoma: case report - Yalikun, Kugeluke (Int J Clin Exp Pathol, 2019)
Introduction: Lymphangioleiomyomatosis (LAM) is a rare disease which affects women of reproductive age almost exclusively as one of the most gender-specific diseases, and which can occur at any site in the body but most commonly in the lungs. Here we report a rare case of recurrent brain lymphangiomyoma which was misdiagnosed as angiomyxoma. Case presentation: A 28-year-old male complained of finding a recurrent mass at the right temporal lobe of his brain for the last 4 months. He had undergone a resection of a brain mass two years prior. One year after the operation, the mass recurred again and was resected another time. Both of the operations were performed in another hospital and he was postoperatively diagnosed with angiomyxoma. This time the patient underwent a third operation in our hospital to remove the lesion, which was confirmed as lymphangiomyoma. Unfortunately, the patient again discovered a re-emerging mass at the primary operation site on the 50(th) day post-surgically. Conclusion: There is currently no effective cure for LAM and treatment options and relevant literature remain limited. Hence other potential therapeutic targets need to be identified.